Arts and Humanities Academics in Schools : Mapping the Pedagogical Interface. - Baker, Geoff (Continuum International Pub. Group, 2011)
In recent years interest in schools outreach and academic enrichment has increased dramatically, reflecting a greater social conscience and awareness of the impact that universities can have on the wider community. The transferable skills that academics bring to schools need to be honed for this new learning environment, as delivery methods and success benchmarks are radically different in a schools context.€This collection address the numerous issues raised when Arts academics become involved with schools, bringing together practitioners from a broad range of fields within the Arts.